Managing COVID-19 through collaboration: applying a novel patient care model in a rural Indian community - Amrit Nanaiah; Frederick Southwick; Venkat Chekuri; Matthew Edwards; Madeline McCabe; Lennox K Archibald; Bopaiah Paruvangada; Gautam Kalyatanda (Inishmore Laser Scientific Publishing Ltd, 2022)
# Background Rural communities in India are vulnerable to the global pandemic of severe acute respiratory coronavirus 2 (SARS-CoV-2) due to a lack of resources and delayed access to information. To address the challenges faced by Primary Health Centers, the Karuna Trust-Lopamudra Medical Center COVID-19 High Dependency Unit (KLCHDU), a collaboration between a local hospital, a non-governmental organization, infectious disease physicians from an academic medical center in the United States, and a local citizens council, was established in May 2021. This collaboration implemented diagnostic and management COVID-19 protocols recommended by the Infectious Diseases Society of America, the National Institute of Health, and the U.S. Centers for Disease Control and provided basic training on recommended practices to Primary Health Center and other local healthcare workers. # Methods All local patients between 1 May 2021 through 31 July 2021 who tested positive for SARS-CoV-2 with a rapid antigen test or polymerase chain reaction test were admitted to the KLCHDU and were included in this study. Patient demographics, medical history, hospital course, and laboratory findings were evaluated to determine the outcomes of patients treated within this unique healthcare model. # Results Eighty-three patients (54% male) qualified for inclusion during the study period. Common comorbidities included hypertension (52%), diabetes mellitus (48%), and coronary heart disease (10%). Nearly one-third of patients had received at least one dose of SARS-CoV-2 vaccine. The most frequently administered hospital medications were dexamethasone (65%), low molecular weight heparin (54%), and remdesivir (53%). The average absolute leukocyte count was 1534 cells/µL, average blood glucose was 182 mg/dL, average D-dimer was 849 ng/mL, and average NEW-2 score on admission and discharge was 4.4 and 3.2. The average duration of hospital stay was five days. Eleven (13%) patients were prescribed supplemental oxygen at discharge and one patient died from infection complications. # Conclusions Our data show a duration of inpatient hospitalization and mortality rate on the lower end of most published data. The results of our study encourage allocation of resources based on recommended protocols and the use of telehealth for collaboration and resource sharing.